CuBr2-catalyzed diastereoselective allylation: total synthesis of decytospolides A and B and their C6-epimers. Issue 14 (23rd March 2020) - Padhi, Birakishore; Reddy, G. Sudhakar; Mallampudi, N. Arjunreddy; Choudhury, Utkal Mani; Mohapatra, Debendra K.
Abstract : An efficient, cost effective and protecting group tolerant CuBr2 -catalyzed synthesis of 2, 6- trans -disubstituted tetrahydropyran with excellent diastereoselectivity, demonstrated in the total synthesis of decytospolides A and B and their C6-epimers. Abstract : An efficient CuBr2 -catalyzed diastereoselective allylation of a cyclic hemiacetal with allyltrimethylsilane as a nucleophile has been developed. The protocol offers a cost effective, protecting group tolerant, and operationally simple approach to 2, 6- trans -disubstituted tetrahydropyran with excellent diastereoselectivity. Furthermore, the application of this methodology has been demonstrated in the total synthesis of decytospolides A and B and their C6-epimers.